Accommodating Bishops. (13th August 2014) - Cranmer, Frank; Pocklington, David
<x content-type="archive" xml:space="preserve">Abstract</x> Earlier this year the Church Commissioners decided that the newly appointed Bishop of Bath and Wells should live in the Old Rectory, Croscombe, instead of at the historic palace in Wells. When the decision met considerable local opposition, not least in the House of Commons, the Archbishops' Council appointed a committee consisting of Mrs Mary Chapman (in the Chair), Philip Fletcher and Archdeacon Cherry Vann to consider objections. After a hearing, the committee directed that the transaction should not proceed.